2017
DOI: 10.1536/ihj.16-627
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Coronary to Pulmonary Artery Fistulas in Adults

Abstract: SummaryCoronary to pulmonary artery fistulas (CPAFs) are abnormal communications between the coronary and pulmonary arteries. They are an uncommon congenital heart disease and usually remain asymptomatic until later in life. However, there is no consensus on their management. We present four adult patients who required surgery for coronary to pulmonary artery fistulas to illuminate this issue. The clinical presentations were variable depending on the anatomical features of coronary to pulmonary artery fistulas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Most CPAF can be classified as the anterior type characterized by connecting the proximal portion of the left or right coronary artery and the anterior wall of the pulmonary artery. In contrast, the posterior type originates from the left circumflex artery or left sinoatrial node artery and drains into the right pulmonary artery via transverse sinus [6]. While CPAF is primarily congenital, it can also result from iatrogenic procedures, trauma, chest radiation, and several diseases like myocardial infarction, Kawasaki disease, and Takayasu arteritis [7,8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most CPAF can be classified as the anterior type characterized by connecting the proximal portion of the left or right coronary artery and the anterior wall of the pulmonary artery. In contrast, the posterior type originates from the left circumflex artery or left sinoatrial node artery and drains into the right pulmonary artery via transverse sinus [6]. While CPAF is primarily congenital, it can also result from iatrogenic procedures, trauma, chest radiation, and several diseases like myocardial infarction, Kawasaki disease, and Takayasu arteritis [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…Large left-to-right shunts could also lead to pulmonary hypertension and induce congestive heart failure [4]. Besides, If other cardiac comorbidities such as patent ductus arteriosus, ventricular septal defect, valvular disease, and coronary atherosclerosis exist, CPAF might exacerbate the concomitant conditions [6]. Moreover, CPAF could complicate coronary aneurysmal dilatation, thrombosis, or infective endocarditis [10].…”
Section: Discussionmentioning
confidence: 99%
“…Surgical correction is recommended for a large, symptomatic fistula presenting with angina pectoris, decompensated heart failure, complications due to significant pulmonary-systemic shunt, hemodynamic compromise, complex anatomy with multiple communications, tortuous pathways, multiple terminations, significant aneurysmal dilatation, or requirement for simultaneous distal bypass. [6,7] In recent decades, transcatheter closure approaches have emerged as a less invasive and effective strategy. [1] The advantages of the transcatheter approach include less morbidity, lower cost, shorter recovery time, and avoidance of thoracotomy and cardiopulmonary bypass.…”
Section: Discussionmentioning
confidence: 99%
“…Even though standardized treatment guidelines for the management of CPAF have not been established, it has been suggested that several factors such as the size of the fistula, hemodynamic changes on echocardiography, the presence of ischemia on myocardial perfusion imaging, and associated cardiac anomalies can be determinants for the choice between conservative treatment and invasive procedures (19). The most commonly used surgical treatment is fistula ligation (2021). However, endovascular interventional procedures can be successfully performed in some cases (2223).…”
Section: Introductionmentioning
confidence: 99%